Improved treatment of recurrent aphthous stomatitis with sodium pentaborate pentahydrate (NaB) (Annals of Medical Research, 2021)
Aim: Chlorhexidine (CHX) and benzydamine hydrochloride (B-HCl) combination treatment (Kloroben™ spray) was compared with sodium pentaborate pentahydrate (NaB, also called boron) treatment with regard to their effects in the recovery of recurrent aphthous stomatitis (RAS). Materials and Methods: We assessed the treatment results by evaluating ulcer radius and VAS results. Seventy-one patients with clinically diagnosed minor RAS were selected for the study based on inclusion and exclusion criteria. Group 1 was treated with a 3% solution of NaB and group 2 was treated with Kloroben spray (45 mg benzydamine HCl and 36 mg chlorhexidine gluconate) for 1 week. Results: After the treatments, there were statistically significant decreases in VAS scores in both Group 1 (p0.001) and Group 2 (p0.001). We found that the decrease in VAS score was greater in Group 1 than in Group 2 (p0.001). Similarly, there were statistically significant decreases in ulcer diameters for both groups. The ulcer diameter reduction was also greater in Group 1 than Group 2 (p0.001). Conclusions: When the specifications of NaB and studies that report its effects are considered, it may be concluded that NaB works well in the healing process of oral aphthae. Our findings show that NaB is better than CHX for the treatment of RAS, which is demonstrated by greater reduction of ulcer diameter and pain score in the NaB group.